Determinants of Unmet Need Family Planning Among Married Woman of Reproductive Age in North Sumatra (Susenas March 2019) - Aprillia Anis Saputri; Rini Rahani (Politeknik Statistika STIS, 2021)
Unmet need is one of the obstacles of the family planning programs that can reduce contraceptive prevalence. The percentage of total unmet need in North Sumatra Province is 12.1 and comparable to the total national unmet need in 2019. This study aims to determine the factors that influence family planning needs and the tendency of married women of reproductive age in North Sumatra Province in 2019 with multinomial logistic regression. The data used is sourced from the Susenas KOR 2019. Results show that married women of reproductive age having a greater tendency to experience the unmet need for limiting are characterize as 35-49 years old, living in urban areas, and with junior high/equivalent levels. Meanwhile, the characteristics of married women of reproductive age (WUS) who have a greater tendency to experience the unmet need for spacing such as aged 15-24 years, Age at First Marriage more than 18 years, and with a higher education level. Therefore, a more optimal commitment and support from family planning field workers in family planning counselling are needed and increase equitable access and quality of family planning services.